2004
DOI: 10.1002/jcb.20012
|View full text |Cite
|
Sign up to set email alerts
|

Ets proteins in biological control and cancer

Abstract: The Ets family consists of a large number of evolutionarily conserved transcription factors, many of which have been implicated in tumor progression. Extensive studies on this family of proteins have focused so far mainly on the biochemical properties and cellular functions of individual factors. Since most of the Ets factors can bind to the core consensus DNA sequence GGAA/T in vitro, it has been a challenge to differentiate redundant from specific functions of various Ets proteins in vivo. Recent findings, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
204
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 32 publications
5
204
0
6
Order By: Relevance
“…28,29 Its expression is highly regulated by the v-ets erythroblastosis virus E26 oncogene homolog 1 (Ets-1) in invasive breast cancer cells. 30 Here, we have shown that Ets-1 was significantly (Po0.01) downregulated by ERp29 (Figure 2a), further supporting a mechanistic link of ERp29 in attenuating uPAR in these slowly proliferating ERp29-transfected cells. Given that activation or loss of the uPAR-b 1 -integrin-EGFR complex decides the fate of the cell between proliferation and growth arrest (Figure 1), we further investigated whether ERp29-mediated cell growth arrest in MDA-MB-231 cells was associated with the interruption of downstream signaling regulated by this complex.…”
Section: Overexpression Of Erp29 Significantly Reduces the Level Of Tsupporting
confidence: 67%
“…28,29 Its expression is highly regulated by the v-ets erythroblastosis virus E26 oncogene homolog 1 (Ets-1) in invasive breast cancer cells. 30 Here, we have shown that Ets-1 was significantly (Po0.01) downregulated by ERp29 (Figure 2a), further supporting a mechanistic link of ERp29 in attenuating uPAR in these slowly proliferating ERp29-transfected cells. Given that activation or loss of the uPAR-b 1 -integrin-EGFR complex decides the fate of the cell between proliferation and growth arrest (Figure 1), we further investigated whether ERp29-mediated cell growth arrest in MDA-MB-231 cells was associated with the interruption of downstream signaling regulated by this complex.…”
Section: Overexpression Of Erp29 Significantly Reduces the Level Of Tsupporting
confidence: 67%
“…As shown in Figure 4a, western blot analyses revealed that rPAUF activated p90RSK, a downstream effector of the ERK signaling cascade (Anjum and Blenis, 2008), and subsequently the p90RSK target transcription factors, CREB and ELK-1. ELK-1 is known to be activated by the ERK and JNK signaling pathways (Hsu et al, 2004). The transcription factors c-Jun and ATF2, which are downstream targets of JNK signaling cascade, were also activated.…”
Section: Pancreatic Adenocarcinoma Upregulated Factor (Pauf) Activatementioning
confidence: 99%
“…Ets proteins constitute a family of conserved sequencespecific transcription factors and share an 85 amino-acid DNA-binding domain, the ETS domain (Graves and Petersen, 1998;Watson et al, 2002;Hsu et al, 2004). Ets factors bind to the GGAA/T core motif (Ets-binding site, EBS) in the enhancer or promoter regions of their target genes (Sementchenko and Watson, 2000;Dittmer, 2003;Obika et al, 2003).…”
Section: Introductionmentioning
confidence: 99%